Morphometric parameters of Phragmites australis as indicators of soil salinity: habitat and remote sensing approach as exemplified by brine-supplied salt marshes in the Parsęta Valley (NW Poland) - Bosiacka, Beata; Pieńkowski, Paweł; Podlasiński, Marek (Ecological Questions, 2011)
The paper illustrates an application of morphometric parameters of common reed to locate saline patches in extensive rush complexes. The study evaluated the applicability of aerial photographs and explored effects of soil salinity on reed stem mean height (r = -0.72) and diameter (r = 0.52).